2018
DOI: 10.1186/s41240-018-0091-2
|View full text |Cite
|
Sign up to set email alerts
|

The pepsinolytic hydrolysate from Johnius belengerii frame inhibited LPS-stimulated production of pro-inflammatory mediators via the inactivating of JNK and NF-κB pathways in RAW 264.7 macrophages

Abstract: The objective of this study was to investigate the anti-inflammatory effects of the pepsinolytic hydrolysate from the fish frame, Johnius belengerii, on lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages. The J. belengerii frame hydrolysate (JFH) significantly suppressed nitric oxide (NO) secretion on LPS-stimulated RAW264.7 macrophages. Moreover, the JFH markedly inhibited the levels of protein and mRNA expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2). Furthermore, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…For example, the polysaccharides have been elucidated to inhibit cellular production of pro-inflammatory mediators through inhibition of NF-κB signaling pathway and reduction in p65 nuclear translocation [ 46 , 47 ]; for example, the garlic extract could reduce the production of NO in the LPS-stimulated RAW264.7 macrophages by inhibiting NF-κB nuclear translocation and HO-1 activation [ 48 ]. In addition, the fishbone protein hydrolysates showed an anti-inflammatory effect on the RAW264.7 macrophages by down-regulating the phosphorylation levels of JNK and NF-κB, resulting in a block in JNK/NF-κB signaling pathways [ 21 ], while lactoferrin could combat against the LPS-induced inflammation in human nasal epithelial cells via inhibition on MEK1/2-MAPK signaling pathway [ 49 ]. Overall, the TLR4/MyD88/NF-κB signaling pathway has attracted widespread attention in the scientific community due to their implant-related innate immune recognition and immuno-modulation [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the polysaccharides have been elucidated to inhibit cellular production of pro-inflammatory mediators through inhibition of NF-κB signaling pathway and reduction in p65 nuclear translocation [ 46 , 47 ]; for example, the garlic extract could reduce the production of NO in the LPS-stimulated RAW264.7 macrophages by inhibiting NF-κB nuclear translocation and HO-1 activation [ 48 ]. In addition, the fishbone protein hydrolysates showed an anti-inflammatory effect on the RAW264.7 macrophages by down-regulating the phosphorylation levels of JNK and NF-κB, resulting in a block in JNK/NF-κB signaling pathways [ 21 ], while lactoferrin could combat against the LPS-induced inflammation in human nasal epithelial cells via inhibition on MEK1/2-MAPK signaling pathway [ 49 ]. Overall, the TLR4/MyD88/NF-κB signaling pathway has attracted widespread attention in the scientific community due to their implant-related innate immune recognition and immuno-modulation [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several bioactive components were reported to mediate the expression of the targeted genes and related proteins in the NF-κB signaling pathway or mediate the expression of several inflammatory cytokines regulating the NF-κB signaling pathway or those suppressing excessive inflammatory responses [ 18 , 19 , 20 ]. For example, the hydrolysates from fish and rice proteins could inhibit NF-κB activation, reduce p65 translocation to the nucleus, block NF-κB signaling pathway, and exert anti-inflammatory function [ 21 , 22 ]. Therefore, the question of whether the plastein reaction (especially that occurs in the presence of exogenous amino acids) can change the anti-inflammatory effect of casein hydrolysates attracts our attention.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we investigated in vitro anti‐inflammatory activity using RAW 264.7 macrophage, commonly used as an appropriate macrophage model and to detect cytotoxicity (Choi et al., 2018; Heo et al., 2018; Kim et al., 2018). Moreover, LPS is an endotoxin that presented in the outer membrane of gram‐negative bacteria, such as Escherichia coli , Pseudomonas aeruginosa , and Klebsiella pneumoniae , and is used as a central inflammatory stimulator on several cell lines (Kim et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LPS is an endotoxin that presented in the outer membrane of gram‐negative bacteria, such as Escherichia coli , Pseudomonas aeruginosa , and Klebsiella pneumoniae , and is used as a central inflammatory stimulator on several cell lines (Kim et al., 2018). Furthermore, LPS triggers macrophage activation and production of inflammatory mediators such as iNOS, COX‐2, nitric oxide (NO), and prostaglandin E 2 (PGE 2 ) (Heo et al., 2018; Nguyen et al., 2016). iNOS is an important inflammatory mediator expressed in various cells and tissues and produces NO (Ren et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that FF is widely used to treat lipopolysaccharide (LPS)-induced inflammation and oxidation ( Lee et al, 2018 ; Shao et al, 2021 ). In response to LPS, macrophages produce NO, which is synthesized by iNOS, increasing the level of nuclear NF-κB as well as pro-inflammatory cytokines such as TNF-α, IL-1β ( Heo et al, 2018 ; Hung et al, 2019 ). It also activates the Nrf2 signaling pathway, resulting in the secretion of antioxidant enzymes such as HO-1 and NQO1 ( Lim et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%